Superhydrophobic plasma polymerized nanosponge with high oil sorption capacity - Torasso, Nicolás (2019)
Oil spills in water cause environmental and economic disasters. Herein, a superhydrophobic and oleophilic carbonaceous nanosponge (CN) with high adsorption capacity for selective oil removal from water was developed. It was grown by plasma polymerization of commercial acetylene in a radio frequency glow discharge (RFGD), a single-step, scalable technique. The CN is a porous network of spherical nanoparticles with a broad pore size distribution. It adsorbs 33 times its own weight of light crude oil, with null water adsorption in shaking conditions (ASTM F726-12). Because the CN could be used under sunlight exposure, the effect of UV light irradiation was studied. Potential applications of the CN arise, as it can be deposited on many substrates and change their wetting properties.